KURIKULUM INTERNASIONAL PENDIDIKAN - Nirsantono Hasnul (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
The purposes of this research were to compare the curriculum of Special Education (PLB) Faculty of Education (FIP), State University of Jakarta (UNJ) with special education curriculum of HNU Programs, China, and to obtain an international curriculum for majors sujects in PLB FIP UNJ in 2010. The research which was conducted at FIP and HNU employed descriptive method and the data were collected using observation and interviews. The comparison between the two universities indicated that the special education curriculum of FIP UNJ is more comprehensive and student’s competency to be achieved consists of five areas: personality development, knowledge and skills, working skills, working behaviors, and social life. The research findings indicate that the international curriculum of Special Education Programs (PLB), FIP, UNJ, can be used for overseas students particularly China who are interested in special education.